'An uplifting tale of Europe'. Jacques Delors and the contradictory quest for a European social model in the Age of Reagan†. (3rd July 2018) - Bitumi, Alessandra
Abstract : Based on the personal papers of Jacques Delors, this article discusses the origins and significance of Delors's ambition to provide a renewed and updated form of socially embedded capitalism, within the framework of the Atlantic Community in the 1980s. Engaging in a political and intellectual battle against 'Reaganism', the President of the European Commission tried to draw the boundaries of Europe's alleged distinctiveness, turning this imagined Europe into a project for the future. The article reveals how the 'Social nature' of Europe, ubiquitously and conveniently opposed to the neoliberal character of US capitalism, has been the pillar of a long popular exceptionalist narrative that became hegemonic, in the EU and progressively worldwide, in the 'age of Delors'.